Integrated genomic and molecular insights into astrocyte- and oligodendrocyte-derived amyotrophic lateral sclerosis: focus on miRNAs and extracellular vesicles: Integrated molecular analysis of glial cells in ALS - Asghari Jafari , Ehsan; Arabi, Maryam; Bereimipour, Ahmad (Cellular and Molecular Biology, 2025)
Motor neurons in the brain and spinal cord begin to die off in Amyotrophic lateral sclerosis (ALS), a disease that can be fatal. Molecular pathways in neurological disease, especially ALS, remain a challenge in the medical sciences. In this disease, a disorder in both astrocytes and oligodendrocytes can cause the disease to progress. This study aimed to investigate the molecular mechanisms and find key elements between these two cells in ALS with a bioinformatics perspective. In this study, using integrated and continuous bioinformatics analytics by various tools and databases, we investigated genes, protein products, and miRNAs between astrocytes and oligodendrocytes. The obtained data were involved in the Cellular senescence, actin cytoskeleton, and cell cycle signaling pathways. Then, after careful evaluation of the information, TP53, MDM2, KRAS, PTPRC, and GSK proteins were candidates, which are regulated by hsa-miR-564, hsa-miR-496-5p, hsa-miR-324-5p, hsa-miR-296-5p, and hsa-miR-4258-3p miRNAs. Finally, the four genes had a more robust and better relationship in this study between astrocyte and oligodendrocyte-derived ALS.